Survey on the Approval and Use of Group 1 Priority Antibiotics at a Provincial Hospital in Vietnam - Lan Huong, Hoang; Hai Bang, Ha; Thi Hong, Nguyen; Thanh Hai, Nguyen; Cat Khanh, Tran; Quoc Anh, Phan; Huy Quan Anh, Dieu; Thi Thu Thuy, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Objective: To analyze the approval process and usage patterns of Group 1 priority antibiotics, namely vancomycin, injectable linezolid, and colistin at Thai Nguyen A Hospital. Methods: A retrospective cross-sectional study was conducted among patients administered Group 1 priority antibiotics for over 72 hours, using inpatient medical records from July to December 2023. Approval procedure: i) Physicians must submit an Antibiotic Use Request Form (AURF) to the Pharmacy Department prior to prescribing these antibiotics, and ii) Clinical Pharmacists check the AURF and may additionally monitor or retrospectively review cases without prior AURF submission.  Results: In 172 patients, Group 1 antibiotics were predominantly utilized for Gram-positive bacteria (90.63%). Regarding dosing, 85.71% of colistin loading doses and 100% of linezolid cases complied with guidelines. However, while 75.0% of vancomycin maintenance doses were appropriate, only 12.5% of patients received an adequate loading dose. In total, 79.07% of patients improved or cured. Clinical pharmacists executed 62 interventions, primarily focused on therapeutic monitoring (50.0%) and regimen adjustments (41.9%). Vancomycin necessitated the most frequent therapy adjustments, while interventions for linezolid and colistin concentrated on monitoring side effects and assessing renal function, respectively. Conclusion: Group 1 priority antibiotics were generally used appropriately, resulting in favorable clinical outcomes. The results highlight the critical role of clinical pharmacist interventions in enhancing antimicrobial stewardship to optimize the use of high-priority antibiotics. Keywords: Group 1 antibiotics, antibiotic stewardship, pharmacist interventions.